Revision of the genus Amputoearinus (Hymenoptera: Braconidae: Agathidinae) with fourteen new species - Lindsay, Cheryl; Sharkey, Michael (Zootaxa, 2006)
Fourteen new species of Amputoearinus are described along with redescriptions for A. matamata Sharkey and A. fernandezi Sharkey. A phylogenetic hypothesis employing morphological characters is proposed for the species of Amputoearinus using three other genera of Agathidinae as outgroups. The fourteen new species are: Amputoearinus alafumidus sp.n., Amputoearinus boringi sp.n., Amputoearinus erudio sp.n., Amputoearinus flavocacumen sp.n., Amputoearinus galbus sp.n., Amputoearinus gloriae sp.n., Amputoearinus niger sp.n., Amputoearinus pectusacutum sp.n., Amputoearinus pitzi sp.n., Amputoearinus planusfunditus sp.n., Amputoearinus seltmannae sp.n., Amputoearinus sharanowskiae sp.n., Amputoearinus surinen sp.n., and Amputoearinus variegatus sp.n.